MANAJEMEN PENILAIAN KINERJA GURU TERHADAP PELAYANAN MUTU PENDIDIKAN DI MAN PULAU TALIABU - pardin (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2023)
The management of teacher performance assessment influences the quality of education at MAN Pulau Taliabu. Teachers with good evaluations sometimes do not fully contribute to teaching and self-development. This study focuses on the management of teacher performance assessment and the quality of education at MAN Pulau Taliabu, using field methods and qualitative analysis. Data were obtained through observation, interviews, and documentation. The purpose of this study is to understand the management of teacher performance assessment's impact on the quality of education in the school and contribute to theoretical and practical understanding. The research findings indicate that the management of teacher performance assessment at MAN Pulau Taliabu has been effective; collaborative efforts are needed to pay attention to human resources with educational quality standards. Conclusion: teacher performance assessment contributes to the quality of education and achieves good accreditation through eight educational quality standards..